2014
DOI: 10.1155/2014/768254
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multiwalled Carbon Nanotube-Reinforced Hydroxyapatite Composites Consolidated by Spark Plasma Sintering

Abstract: Pure HA and 1, 3, 5, and 10 vol% multiwalled carbon nanotube- (MWNT-) reinforced hydroxyapatite (HA) were consolidated using a spark plasma sintering (SPS) technique. The relative density of pure HA increased with increasing sintering temperature, but that of the MWNT/HA composite reached almost full density at 900°C, and then decreased with further increases in sintering temperature. The relative density of the MWNT/HA composites increased with increasing MWNT content due to the excellent thermal conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Higher biodegradability Poor mechanical properties Neo et al, 1993;Shue et al, 2012;Kim et al, 2014;Singh et al, 2016;Lu et al, 2019 Biphasic calcium phosphate BCP Mixture of HA and TCP Osteoconduction Osteoinduction Biocompatibility Proper biodegradability…”
Section: Hydroxyapatite (Ha): a Commonly Used Biosimilar Inorganic Mamentioning
confidence: 99%
“…Higher biodegradability Poor mechanical properties Neo et al, 1993;Shue et al, 2012;Kim et al, 2014;Singh et al, 2016;Lu et al, 2019 Biphasic calcium phosphate BCP Mixture of HA and TCP Osteoconduction Osteoinduction Biocompatibility Proper biodegradability…”
Section: Hydroxyapatite (Ha): a Commonly Used Biosimilar Inorganic Mamentioning
confidence: 99%
“…The modification of CNTs with HAp proved to be helpful in developing a strong interfacial bond and a homogenous dispersion in the matrix, which led to enhanced biological as well as mechanical properties, as the flexural strength was found to be higher (1.6 times) than that of pure HAp. Kim et al [ 99 ] reinforced HAp with different percentages of multiwalled carbon nanotubes and utilised the spark plasma sintering (SPS) technique for consolidation. Sintering at 900 °C, the composite attained maximum density, fracture toughness, and Vickers microhardness, but sintering beyond this temperature led to a degradation of the properties.…”
Section: Carbon and Its Structuresmentioning
confidence: 99%
“…Kalmodia et al [ 145 ] manufactured a HAp -Alumina (Al 2 O 3 ) -multiwalled carbon nanotubes (CNTs) composite. Previous, separate studies showed an enhancement of fracture toughness of the HAp matrix using individual Al 2 O 3 reinforcement [ 146 , 147 ] and CNT reinforcement [ 72 , 93 , 98 , 99 ]. In this study, researchers were interested in investigating the combined reinforcing effect of CNT and Al 2 O 3 in a HAp matrix.…”
Section: Other Systems Involving Carbon Structures and Hydroxyapatmentioning
confidence: 99%
“…Among several filler materials, carbon nanotubes (CNTs) possess attractive properties that have demonstrated great potential to be incorporated in composites with metals, ceramics, and polymers . Owing to the good mechanical properties of CNTs, they have been used as reinforcement materials in a PTFE matrix to form PTFE–CNT composite materials.…”
Section: Introductionmentioning
confidence: 99%